Advanced continuous-flow microfluidic device for parallel screening of crystal polymorphs, morphology, and kinetics at controlled supersaturation. Issue 12 (7th June 2021) - Coliaie, Paria; Kelkar, Manish S.; Langston, Marianne; Liu, Chengxiang; Nazemifard, Neda; Patience, Daniel; Skliar, Dimitri; Nere, Nandkishor K.; Singh, Meenesh R.
Abstract : An advanced continuous-flow microfluidic device for rapid, parallel screening of crystalline materials, which can profoundly impact the discovery and development of active pharmaceutical ingredients and other crystalline materials. Abstract : A flow-controlled microfluidic device for parallel and combinatorial screening of crystalline materials can profoundly impact the discovery and development of active pharmaceutical ingredients and other crystalline materials. While the existing continuous-flow microfluidic devices allow crystals to nucleate under controlled conditions in the channels, their growth consumes solute from the solution leading to variation in the downstream composition. The materials screened under such varying conditions are less reproducible in large-scale synthesis. There exists no continuous-flow microfluidic device that traps and grows crystals under controlled conditions for parallel screening. Here we show a blueprint of such a microfluidic device that has parallel-connected micromixers to trap and grow crystals under multiple conditions simultaneously. The efficacy of a multi-well microfluidic device is demonstrated to screen polymorphs, morphology, and growth rates of l -histidine via antisolvent crystallization at eight different solution conditions, including variation in molar concentration, vol% of ethanol, and supersaturation. The overall screening time for l -histidine using the multi-well microfluidic device is ∼30 min, which is at least eight times shorter than the sequential screening process. The screening results are also compared with the conventional 96-well microtiter device, which significantly overestimates the fraction of stable form as compared to metastable form and shows high uncertainty in measuring growth rates. The multi-well microfluidic device paves the way for next-generation microfluidic devices that are amenable to automation for high-throughput screening of crystalline materials.